The Involvement of Purinergic System in Pain: Adenosine Receptors and Inosine as Pharmacological Tools in Future Treatments - Nascimento, Francisney Pinto; Jr., Sérgio José Macedo; Santos, Adair Roberto Soares (IntechOpen, 2012)
None